2020
DOI: 10.5109/2740936
|View full text |Cite
|
Sign up to set email alerts
|

“Do humans play according to the game theory when facing the social dilemma situation?” A survey study.

Abstract: The aim of this study is to verify whether a human can detect the social dilemma class and its strength for four various games: Prisoner's dilemma, Trivial, Chicken, and Stag-Hunt by using a web-based structural cross-sectional survey. We considered respondent's cooperative and defective behavior by designing multiple sets of 2 × 2 games for two classes in terms of game opponents: whether he is an intimate friend or an unknown person in the questionnaire. In total, 375 respondents participated in this survey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…One concern is the external validity of our findings. While it has been shown that people can easily identify PD games and play according to the game theory in the lab [ 42 ], it is possible that the same individuals may behave differently when facing a similar social dilemma in the real-world. It also remains to be seen whether our results can be generalised to other types of health measures such as vaccine passports and social distancing—scenarios where the stakes are large and interactions are repeated across countries and stages of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…One concern is the external validity of our findings. While it has been shown that people can easily identify PD games and play according to the game theory in the lab [ 42 ], it is possible that the same individuals may behave differently when facing a similar social dilemma in the real-world. It also remains to be seen whether our results can be generalised to other types of health measures such as vaccine passports and social distancing—scenarios where the stakes are large and interactions are repeated across countries and stages of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A survey reported a disruption of agricultural product supply chains attributable to poorer purchaser demand (78%) and the lack of transportation (41%; Hasnin, 2020 ). Closed warehouses (fish arat ) were another reason for a lower fish harvesting rate, noting the associated smaller quantity of fish as food, also leading to lower incomes for the fisher communities (Habib, 2020 ). Fish farmers also experienced economic losses, with Nazrul ( 2020 ) reporting a 20%–50% loss in earnings for fish farmers in the country.…”
Section: Resultsmentioning
confidence: 99%
“…There is a chance to reboot the framework in a manner to abstain from coming back to the past and put resources into a recuperation that fastens vitality progress. An orderly way to deal with the progress of vitality would require concurrent activities on different factors, for example, flowing of the economy, cutting outflows from fossil fuels, human capital structure and sustainable power source for the future energy frameworks [32][33][34][35] .…”
Section: Future Of Indiamentioning
confidence: 99%